Navigating agency problems in corporate law: A Comparative study through the lens of law and economics - Hirimburegama, Yasith (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2023)
This interdisciplinary research explores agency problems within corporate law, through the lens of comparative law and law and economics. By expanding these distinctive yet complementary perspectives, this complex entity can be more easily understood. Here the approach departs from traditional company law strategies and instead unites an economic evaluation of legal norms with a comparative examination of various jurisdictions, thus offering a novel view on how to better solve agency problems. To discern and combine effective legal strategies from diverse jurisdictions, this research also capitalises on comparative law methodology. Based on the strengths of different legal cultures it creates a framework, grounded in law and economics - tertium comparationis -, that can be used to assess and address the second and third agency problems. After analysing the second agency problem, this research proposes the integration of shareholder costs within transaction cost theory. It recommends enhancing cost-efficiency in corporate governance, facilitated by bolstering fiduciary duties, promoting transparency, and endorsing proactive dispute resolution. A proposal emerging from this research introduces a mechanism for prosocial investors to voice their interests in the company, safeguard economic rights and empower minority shareholders. In addition to the second agency problem, the third agency problem is explored, redefining a company’s purpose to mirror public interest and balance socio-economic prosperity with environmental sustainability. The research introduces stakeholder costs in transaction cost theory, underlining the long-term value increase of incorporating stakeholder rights as monitoring costs. Here, emphasis is placed on the importance of aligning businesses with the provisional nine planetary boundaries and establishing a robust social foundation, as inspired by the Doughnut Economics model. The research suggests regulatory mechanisms to categorise businesses based on their environmental impact and advocates for all companies, irrespective of their size or sector, to adhere to high sustainability standards. In conclusion, the research combines comparative law methodology with law and economics, and proposes legal strategies that address agency problems, promote efficiency, and advocate for environmental sustainability. It exemplifies the potential of this combined approach to reshaping the corporate landscape to better reflect public interest while upholding the principles of the Doughnut Economics model.